ANALISIS PENGARUH HARGA, PROMOSI, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN - Emawati; Raspati, Jo Eddy; Hamzah, Muhammad Ichwan (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
This study aims to determine the influence of price, promotion, and service quality on customer satisfaction. This study uses primary data with a total sample of 30 subjects were obtained from a population, that is customers who have purchased more than one time. The analysis tool used is multiple regression using SPSS for Windows version 22.0. Results of this study indicate the F test that price, promotion, and service quality simultaneous significant influence on customer satisfaction with value Sig 0.000 and value Fcount > Ftable (54.738 > 2.98). Results of the t test (partial) shows that prices have a significant effect on customer satisfaction with value Sig 0.025 and the value tcount > ttable (2.377 > 2.056), the promotion had no significant effect on customer satisfaction with value Sig 0,282 and the value tcount < ttable (1.099 < 2.056) and service quality significantly influence customer satisfaction with value Sig 0.000 and the value tcount > ttable (6.009 > 2.056). It can be concluded that the promotion had no significant effect on customer satisfaction, while price and service quality have a significant effect partially on customer satisfaction. Price, promotion, and quality of service have a significant effect simultaneously on customer satisfaction.